Determination of hydroquinone in pure form and pharmaceutical preparations using Batch and FIA-Merging Zone techniques with spectrophotometric detection - B.Al-Mosulli, Bushra; S.Al-Jomaili, Aseel; S.Al-Janabi, Hamssa (Iraqi Journal of Science, 2023)
In this study, a new, rapid and sensitive batch and flow injection-merging zones spectrophotometric methods for the determination of hydroquinone in a pure material and in pharmaceutical preparation were proposed. These methods were based on the oxidative-coupling reaction of HQ with 2,4-dinitrophenylhydazine (DNPH) in the presence of sodium periodate and sodium hydroxide to form a dark brown water slouble dye that is stable and has maximum absorption at 530 nm, graphs of absorbance versus concentration show that Beer’s low is obeyed over the concentration rang of 1-40 and 3-300 μg.ml-1 of hydroquinone, with detection limits of 0.162 and 0.510 μg.ml-1 of hydroquinone for batch and FIA methods, respectively. The optimized FIA system is able to determine hydroquinone with a through put of 83 h-1. All different chemical and physical experimental parameters affecting on the development and stability of the colored product were carefully studied and the proposed methods were successfully applied for the determination of hydroquinone in pharmaceutical preparations.